2015
DOI: 10.1167/iovs.15-16588
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Soluble Fas Ligand Ameliorates Acute and Recurrent Herpetic Stromal Keratitis in Mice

Abstract: This study provides evidence that sFasL treatment has potential therapeutic benefit in reducing inflammatory infiltrate and neovascularization in primary and recurrent forms of HSK, and that it does so by augmenting the restriction of Fas+ inflammatory cells mediated by membrane FasL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…It is possible that immune control mediated via sFas-L contributes to the moderate disease phenotype by preventing immunopathology. Supporting this hypothesis, administering sFas-L improved clinical outcome in herpes simplex virus-mediated keratitis, presumably by activating apoptosis of inflammatory cells [30]. The finding that TNFR-II is released in soluble form by T-regulatory cells and can control IL-6-mediated inflammation [31] adds further credence to the idea of immune control playing a critical role in controlling EBOV clinical severity.…”
Section: Immune Modulation and Evdmentioning
confidence: 92%
“…It is possible that immune control mediated via sFas-L contributes to the moderate disease phenotype by preventing immunopathology. Supporting this hypothesis, administering sFas-L improved clinical outcome in herpes simplex virus-mediated keratitis, presumably by activating apoptosis of inflammatory cells [30]. The finding that TNFR-II is released in soluble form by T-regulatory cells and can control IL-6-mediated inflammation [31] adds further credence to the idea of immune control playing a critical role in controlling EBOV clinical severity.…”
Section: Immune Modulation and Evdmentioning
confidence: 92%
“…Necrotizing stromal keratitis (NSK) is induced by the recurrent attacks of discoid or dendritic keratitis, which results from the infection of herpes simplex virus in corneal stromal cells [12,13]. NSK is clinically characterized by delayed hypersensitivity, including corneal neovascularization and severe inflammatory cell infiltration [14]. NSK might result in descemetocele, hypopyon, corneal perforation, and even mixed infection, with extremely poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of salivary glands T cells was decreased in SS patients [ 34 ]. It was demonstrated that sFasL treatment has potential therapeutic benefit in reducing inflammatory infiltrate and neovascularization in primary and recurrent forms of herpetic stromal keratitis and that it does so by augmenting the restriction of Fas+ inflammatory cells mediated by membrane FasL [ 35 ]. Previous study also provided evidence that sFasL could be related to the mechanism involved in the elimination of the parasite [ 36 ].…”
Section: Discussionmentioning
confidence: 99%